Clinically-Irrelevant Positivity for Serum Proteinase 3-ANCA in HIV Disease. (October 2013) - Romano, C.; Sellitto, A.; Restivo, L.; Adinolfi, L.E.
Diagnosis of small-vessel vasculitides (granulomatosis with polyangiitis, microscopic polyangiitis, Churg-Strauss syndrome, and their localized forms) is aided by the detection of serum antineutrophil cytoplasmic antibodies (ANCA). However, serum ANCA positivity does not always mean vasculitis. Here, we report on a 61-year-old female patient with very high serum levels of proteinase 3 ANCA, marked hypergammaglobulinemia, low complement levels, and a 16-mm lung nodule on chest CT scan, who was referred to our Institution with a provisional diagnosis of possible granulomatosis with polyangiitis. On admission, history-taking disclosed two recent episodes of viral reactivation (namely, cytomegalovirus and varicella-zoster virus), while physical examination revealed lingual and nail involvement suggestive of Candida infection. An immunodeficiency disorder was eventually suspected. Search for antibodies against human immunodeficiency virus (HIV) 1 and 2 turned positive. Western blot analysis confirmed HIV infection. Thus, although ANCA detection may be helpful in diagnosing small-vessel vasculitis in the appropriate clinical scenario, screening for HIV infection should sometimes be considered to discriminate clinically irrelevant serum ANCA positivity.